Chiroptera as agents of maintenance of urban green spaces - Silva, Rosângela Margarida da; Silva, Luiz Augustinho Menezes da; Lyra-Neves, Rachel Maria de; Telino Júnior , Wallace Rodrigues (ANAP Brazil, 2025)
ABSTRACT Objective - The objective of this study was to survey the richness and abundance of bat species in three green areas of the municipality of Garanhuns, PE, highlighting the importance of these animals in urban ecosystems. Methodology - The study was conducted in three green areas: the Campus of the Federal University of the Agreste of Pernambuco (UFAPE), Ruber Van Der Linden Park, and Colégio Presbiteriano XV de Novembro. Bimonthly captures were carried out between 2022 and 2023, covering two seasons of the year: the dry season (September, November, January) and the rainy season (April, June, August). The captures were performed using mist nets measuring 12m x 2.5m, positioned 30 cm from the ground, opened from 5:00 PM to 12:00 AM, and checked every 15 minutes for two consecutive days in each research area. Originality/relevance - There is a lack of studies on the presence of these animals in urban green areas of the municipality, emphasizing the importance of contributing to the knowledge of the local chiropteran fauna and highlighting the role of urban green areas in bat conservation. Results - A total of 267 bats were captured, distributed among 10 species, with Artibeus lituratus (46.28%) being the most frequently captured species. Theoretical/methodological contributions - The study presents a methodological approach to chiropteran monitoring that can be replicated in other urban areas, contributing to future conservation and environmental management actions. Social and environmental contributions - The study raises awareness of the importance of urban green areas for biodiversity conservation, highlighting the need for public policies focused on integrating nature-based solutions into urban planning.